Development of Portable Biofeedback Devices for Sport Applications - Zulkifli, Ahmad@Manap; Tan, Choon Mong (Springer, 2016)
The purpose of this project is to propose a portable low cost of ECG and EMG devices that plays the role of continuous monitoring of the user heart rate and muscle activity. Recording and analysis of biological signal like Electrocardiography (ECG) and Electromyography (EMG) are important in the field of healthcare and sports which enable to assess the physiological state and training progress of athlete. Heart rate can reflect individual natural fitness whereas the EMG signal indicates muscle activation and fatigue level thus determine the performance. However, most of the EMG and heart rate measuring tools are expensive and large in size. The process of data collection also often confined to hospital or biomechanics lab. Therefore, the development of this monitoring system capable provides immediate feedback about physiological data which is desired by athletes and trainers. The monitoring system is knitted with a pulse sensor and muscle sensor V3. Arduino Uno was act as microcontroller to analyze the collected signal then transmits the data via Bluetooth to Android based smartphone; Laptop through Processing software; or LCD screen. The significant of using Processing software is allow display the data in graphical way. The pulse sensor is applying photoplethsmography (PPG) technique to measure the heart rate in beats per minute (bpm). In other hand, the EMG signal will be collected by passive electrode which allows the monitoring of user muscle stress. Throughout the ECG experiment, the pulse sensor result collected via Coolterm application was compared to radial pulse and Treadmill. The result showed that the error rate of the device is negligible and promising. While the EMG data produced by muscle sensor is achieving a full wave rectified waveform that demonstrates the forearm strength produced.